2001
DOI: 10.1002/clc.4960240610
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose combination therapy with colesevelam hydrochloride and lovastatin effectively decreases low‐density lipoprotein cholesterol in patients with primary hypercholesterolemia

Abstract: SummaryBdCqrowid: Colesevelam hydrochloride is a novel, lipidlowering agent that binds bile acids with high afiinity. A multicenter, randomized, double-blind, placebo-controlled, parallel-design study was conducted to assess the efficacy and tolerability of combination low-dose colesevelam and lovastatin treatment in patients with primary hypercholesterolemia.Hypothesis: Combination therapy with low doses of colesevelam and lovastatin decreases low density (LDL) cholesterol with minimal adverse events.Mef/iodT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 34 publications
2
70
0
1
Order By: Relevance
“…The influence of viscous fiber intake on the LDL-C level is due, at least in part, to inhibition of intestinal absorption/reabsorption of cholesterol and, to a lesser extent, bile acids (Carr et al, 1996;Reppas et al, 2009). The effects of plant sterols and stanols, bile acid sequestrants (for example, colesevelam HCl) and cholesterol absorption inhibitors (for example, ezetimibe) on LDL-C also appear to be additive to the effects of statin therapy (Davidson et al, 2001;Ballantyne et al, 2005;Pearson et al, 2005;Castro Cabezas et al, 2006;Goldberg et al, 2006). The consistency of results across studies suggests that agents that work through interference with the enterohepatic circulation of cholesterol and bile acids produce effects on LDL-C that are directly additive to those of statins.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of viscous fiber intake on the LDL-C level is due, at least in part, to inhibition of intestinal absorption/reabsorption of cholesterol and, to a lesser extent, bile acids (Carr et al, 1996;Reppas et al, 2009). The effects of plant sterols and stanols, bile acid sequestrants (for example, colesevelam HCl) and cholesterol absorption inhibitors (for example, ezetimibe) on LDL-C also appear to be additive to the effects of statin therapy (Davidson et al, 2001;Ballantyne et al, 2005;Pearson et al, 2005;Castro Cabezas et al, 2006;Goldberg et al, 2006). The consistency of results across studies suggests that agents that work through interference with the enterohepatic circulation of cholesterol and bile acids produce effects on LDL-C that are directly additive to those of statins.…”
Section: Discussionmentioning
confidence: 99%
“…The first major clinical study to demonstrate that primary prevention reduced coronary events, the Lipid Research Clinics Coronary Primary Prevention Trial, used the bile acid sequestrant cholestyramine [68,69]. Added to statins, sequestrants achieve a greater reduction in LDL levels than doubling the dose of a statin [68,70,71]. …”
Section: Dyslipidemia Treatmentmentioning
confidence: 99%
“…49 Mean serum LDL-c levels were reduced by 32% to 34% in both combination therapy groups compared to monotherapy with colesevelam or lovastatin (−7% versus −22%, respectively). A significant increase in serum HDL-c levels occurred only in the colesevelam monotherapy group (5%).…”
Section: Combination With Statinsmentioning
confidence: 89%
“…Colesevelam also decreased C-reactive protein by 19% and LDL-particle number by 14% in the single trials in which they were measured. 49 Davidson et al, in a multicenter, randomized clinical trial, demonstrated a dose-dependent LDL-c reduction from baseline in the colesevelam groups (−2% to −19%).…”
Section: Efficacy Monotherapymentioning
confidence: 94%